Looking for Skills in the Former Yugoslav Republic Macedonia - World Bank (World Bank, Washington, DC, 2017)
This report presents new insights on the availability and demand for skills, drawing on two innovative surveys: a household level survey to measure the supply of skills in the adult population, and an employer survey to measure demand for skills. The key message coming from these two surveys is that there is indeed a significant skills gap in the former Yugoslav Republic of Macedonia, and that closing this gap will be beneficial to workers, firms, and the economy. Skills development systems in the former Yugoslav Republic of Macedonia are not equitable, and especially those of non-Macedonian ethnicity lack access to skills development and higher skilled jobs. Access to education still differs significantly across ethnic groups, and the gap does not appear to fall over time. Some more vulnerable groups in the former Yugoslav Republic of Macedonia consequently accumulate fewer skills - even elementary skills such as basic literacy - and have less access to skilled jobs. The skills development system of the former Yugoslav Republic of Macedonia will be strengthened by stronger coordination and collaboration between these different actors. Tax exemptions and other forms of financial incentives could be used to encourage firms to train their work force. However, policy could also focus on connecting employers and educational institutions better, by establishing coordination mechanisms and supporting industrial associations. As part of this agenda, it would be useful to explore ways of introducing apprentice- and internships systems, that expose students with the world of work and increases the practical content of training, while lowering the cost to firms. Efforts to establish labor market information systems in the former Yugoslav Republic of Macedonia, that could help students, workers, employers and educational systems exchange relevant and timely information, are ongoing. A more comprehensive system for monitoring and evaluation would help policy makers identify bottlenecks and quality problems.